2005
DOI: 10.1093/toxsci/kfi326
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cytochrome P450 1A5 mRNA, Protein and Enzymatic Activities by Dioxin-Like Compounds, and Congener-Specific Metabolism and Sequestration in the Liver of Wild Jungle Crow (Corvus macrorhynchos) from Tokyo, Japan

Abstract: This study presents concentrations of polychlorinated dibenzo-p-dioxins (PCDDs), dibenzofurans (PCDFs), and dioxin-like coplanar PCBs (Co-PCBs) in the liver and breast muscle of jungle crows (JCs; Corvus macrorhynchos) collected from Tokyo, Japan. 2,3,7,8-Tetrachlorodibenzo-p-dioxin toxic equivalents (TEQs) derived by WHO bird-TEF were in the range of 23 to 280 pg/g (lipid) in the liver, which are lower or comparable to the lowest-observed-effect-level of CYP induction in chicken, and 5.6-78 pg/g (lipid) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 39 publications
7
21
1
Order By: Relevance
“…The concentration ratios of certain congeners (congener x/PCB169) had negative correlations with CYP1A-like protein content, possibly as a result of preferential metabolism, as reported for some other species [14,15,40]. In pigs, the concentration ratio of PCB114 showed a significant negative correlation with CYP1A-like protein levels (r ¼ À0.44, p < 0.05).…”
Section: Drcs In Pig Livers and Toxicological Significancesupporting
confidence: 61%
See 1 more Smart Citation
“…The concentration ratios of certain congeners (congener x/PCB169) had negative correlations with CYP1A-like protein content, possibly as a result of preferential metabolism, as reported for some other species [14,15,40]. In pigs, the concentration ratio of PCB114 showed a significant negative correlation with CYP1A-like protein levels (r ¼ À0.44, p < 0.05).…”
Section: Drcs In Pig Livers and Toxicological Significancesupporting
confidence: 61%
“…Interspecies comparison of the L/A (or liver-to-muscle) ratios showed that the capacity for hepatic sequestration of DRCs in pigs was comparable to that in the raccoon dog [16] but higher than the capacities in the Baikal seal [12], common cormorant [13], and jungle crow [15].…”
Section: Body Distribution Of Drcsmentioning
confidence: 95%
“…Alkoxyresorufin O-dealkylase (AROD) activities, including EROD, MROD and BROD activities, are typical catalytic markers for a variety of CYP450 enzymes, and thus have great potential to elucidate CYP450 induction by chemical exposure. Among them, EROD activity has been used extensively as a sensitive indicator of the effects of exogenous compounds on CYP1A induction in avian species (Kubota et al, 2006;Verbrugge et al, 2001;Watanabe et al, 2005). Our study revealed that PCP increased EROD activity in the 0.5 mg/(kg·day) PCP exposure group (p < 0.05) (Fig.…”
Section: Effect Of Pcp On Activities Of Alkoxyresorufin O-dealkylase mentioning
confidence: 54%
“…CYP1A5, the avian CYP1A2 ortholog, also selectively binds and sequesters PCBs (Watanabe et al, 2005). Interestingly, non-halogenated hydrocarbon CYP1A inducers may not be subject to CYP1A2 sequestration, as evidenced by a lack of sequestration for indole-3-carbinol, a tryptophan related AhR ligand (Anderton et al, 2004).…”
Section: Sequestration Of Tcdd and Pcbs Cyp1a2 Selectively Binds To mentioning
confidence: 99%